How Early can Embodied Responses be? Issues in Time and Sequentiality. Issue 4 (21st April 2021) - Mondada, Lorenza
ABSTRACT: Focusing on request sequences, this article explores dynamics of projection and anticipation, enabling participants to produce early responses to requests. In particular, the analyses highlight the importance of multimodal formatting and the specific temporalities of multiple multimodal resources for the emergence of projections and the possibility to anticipate an ongoing action. Moreover, the analyses pinpoint the relevance of the local ecology and the praxeological context for the participants, enabling them to anticipate the next relevant action. These features characterizing the temporality of multimodal Gestalts, the relevance of the local ecology, and the details of the praxeological context make it possible for participants to produce very early responses and also to accomplish an action even before it has been actually requested.